Epitaxial κ-Ga2O3/GaN heterostructure for high electron-mobility transistors. (February 2023) - Kang, Ha Young; Yeom, Min Jae; Yang, Jeong Yong; Choi, Yoonho; Lee, Jaeyong; Park, Changkun; Yoo, Geonwook; Kyu Chung, Roy Byung
Abstract: GaN power technology, especially AlGaN/GaN high electron-mobility transistors (HEMTs), has made significant progress in recent years. However, the performance of HEMTs is still limited due to a trade-off between on-resistance and off-state breakdown voltage (BV). Integrating a polar gate dielectric with GaN HEMTs can potentially improve both sheet resistance of the two-dimensional electron gas channel and the field distribution between gate and drain. In this regard, orthorhombic κ-Ga2 O3 has attractive properties since it is predicted to be strongly polar and highly dielectric while it grows epitaxially on GaN. By successfully integrating crystalline κ-Ga2 O3 on GaN HEMTs, the channel sheet resistance is reduced by 20% from a reference device with amorphous Al2 O3 gate dielectric. As a result, the cut-off frequency increases from 4.8 to 9.1 GHz. The dielectric property of κ-Ga2 O3 also improves BV from 354 to 380 V by reducing the peak electric field in the gate-drain region.